The differential effects of technology and trade on female and male workers in India - Sharma, Shruti (Asian Development Bank Institute, 2019)
This paper uses the task content model of occupations to investigate whether technology and trade have had differential effects on male and female workers in India. It describes trends in employment shares and wages for female and male workers based on whether they have routine manual, routine cognitive, or non-routine cognitive occupations. It finds that, though there are some similarities in the broad trends for both female and male workers, such as the fact that those with routine cognitive occupations for both categories have the smallest employment shares, there are also important differences. An investigation into the changes in employment shares reveals that female workers suffer less of a decline in routine cognitive jobs within industry than male workers. Furthermore, male workers experience a bigger increase in demand than female workers due to more jobs within industries that intensively employ workers in non-routine cognitive occupations. The findings in this paper have important implications for labor market policies that target skill development in developing countries.
10419/222798
Keywords: Graue Literatur; occupational choice; tasks; wages; employment; skills; economics of gender